2018
DOI: 10.1177/0363546517753376
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Comparison of Fifth Metatarsal Jones Fracture Fixation Methods

Abstract: Early return to play among athletes before Jones fracture union is associated with increased risk of failure. This study introduces a plantar-lateral plating construct that performed more favorably than intramedullary screw fixation when applied to simulated Jones fractures in cadaveric foot specimens. Further clinical comparative studies are needed to assess the clinical use of this construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
0
38
0
4
Order By: Relevance
“…Several studies evaluated different fixation methods for surgical Jones fracture treatment in various biomechanical test setups. 2,5,8,12,[14][15][16][17][25][26][27]31,[38][39][40][41] Recent attention has been focused on Jones fracture-specific implants such as specifically designed screws and plates. 2,4,16,20,31,32,40,41 Latest biomechanical studies revealed contradictory results comparing Jones fracturespecific screw to plate fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies evaluated different fixation methods for surgical Jones fracture treatment in various biomechanical test setups. 2,5,8,12,[14][15][16][17][25][26][27]31,[38][39][40][41] Recent attention has been focused on Jones fracture-specific implants such as specifically designed screws and plates. 2,4,16,20,31,32,40,41 Latest biomechanical studies revealed contradictory results comparing Jones fracturespecific screw to plate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,8,12,[14][15][16][17][25][26][27]31,[38][39][40][41] Recent attention has been focused on Jones fracture-specific implants such as specifically designed screws and plates. 2,4,16,20,31,32,40,41 Latest biomechanical studies revealed contradictory results comparing Jones fracturespecific screw to plate fixation. 8,10,14,16,17,[23][24][25][26][27][28]40,41 The comparison of two intramedullary screw constructs was technically more appealing to us because the clinical use of percutaneous screw placement is generally accepted as gold standard treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O advento mais recente das placas plantares laterais tem ganhado destaque. Segundo estudo cadavérico de Duplantier et al (12) , esse método de fixação apresentou valor mais elevado de ciclos para falha, força de pico maior para falha e menor gap imediatamente antes da falha do implante, quando comparado aos obtidos pelo parafuso intramedular. Bernstein et al (11) também mostraram resultados promissores no tratamento de 08 atletas de elite com fraturas primárias ou refraturas da base do quinto metatarso.…”
Section: Discussionunclassified
“…Das formas de tratamento cirúrgico possíveis destaca--se a fixação com parafuso intramedular, opção mais aceita atualmente para as fraturas das zonas II e III em atletas (9,10) , podendo estar associada ou não à utilização de enxerto ósseo autólogo, considerando-se a vascularização mais frágil dessas fraturas e o tempo decorrido da lesão até o tratamento. Tem-se mais recentemente dado destaque à utilização de placas plantares para o tratamento dessas lesões (11,12) . O objetivo desse trabalho é avaliar o resultado funcional de jogadores de futebol profissionais submetidos ao tratamento cirúrgico das fraturas da base do quinto metatarso nas zonas II e III de Dameron com parafuso intramedular, com ou sem enxerto ósseo.…”
Section: Introductionunclassified